Undrained shear strength of soft clay reinforced with acrylonitrile butadiene styrene (ABS) column - N Thevagar, Nedunchelian (2024)
Clay soil is one of the troublesome soils encountered by engineers. It presents a major danger to the foundations of light structures. Granular columns have been effective in solving difficulties with foundation stability and settlement as well as in making soft clay more suitable for foundation building. The goal of this study is to determine whether adding Acrylonitrile Butadiene Styrene (ABS) to soft kaolin clay increases its shear strength. There is no studies been done by researches with ABS in ground improvement studies. In addition, physical, mechanical and morphological properties of kaolin (soft clay) and ABS must be identified first. The kaolin as soft clay was reinforced with ABS columns, and tested under Unconfined Compression Test (UCT) and Unconsolidated Undrained Test (UU). For UCT, total of 10 batches of samples including kaolin as control sample had been tested to identify the shear strength. Each batch consists of five samplings to find the average maximum stress. The diameter of column used in this study were 8mm, 12mm and 16mm.Whereas, the penetration depth ratio used were 0.5, 0.75 and 1.0. The biggest improvement in shear strength occurred for column with diameters of 8 mm, 12 mm, and 16 mm during the height penetration ratio was 0.5, with values of 102.94%, 48.56%, and 50.02%. The UCT results revealed a fall and subsequently a rise in the volume replacement ratio, as well as an increase in column height. The Unconsolidated Undrained Test was used to evaluate the shear strength of soft clay reinforced with an ABS column. The cell pressure used were 50kPa, 100kPa and 200kPa with same column diameter specifications as UCT. The friction angle, υ increased significantly from 8.92% to 18.21%. However, there was an improvement in cohesiveness, c, which increased from 4.54% to 45.45%. Columns with ABS improves the strength of clay samples but is dependent on a variety of characteristics.